The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph191610155
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Physical Fitness Index and Body Mass Index in Tibetan Children and Adolescents in Different High-Altitude Areas: Based on a Study in Tibet, China

Abstract: Objective: To investigate the relationship between physical fitness index (PFI) and body mass index (BMI) of Tibetan children and adolescents in different high-altitude areas in Tibet, China. Methods: Using the stratified cluster sampling method, 3819 Tibetan children and adolescents from three different high-altitude areas including Nyingchi, Lhasa and Nagqu in the Tibet area of China were given grip strength, standing long jump, sitting forward bend, 50 m running and endurance running tests. One-way analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The specific calculation of the Z -score for each physical fitness test was (test value-national average)/national standard deviation; the shorter the time for the 50 m run, 1,000 m run for boys, and the 800 m run for girls, the better the performance. Therefore, the PFI was—Z pull-ups or 1-min sit-ups + Z standing long jump + Z seated forward bend- Z 50 m running- Z 1,000/800 m running ( 11 , 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific calculation of the Z -score for each physical fitness test was (test value-national average)/national standard deviation; the shorter the time for the 50 m run, 1,000 m run for boys, and the 800 m run for girls, the better the performance. Therefore, the PFI was—Z pull-ups or 1-min sit-ups + Z standing long jump + Z seated forward bend- Z 50 m running- Z 1,000/800 m running ( 11 , 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Body mass index (BMI) is universally considered a marker of health and is widely used to measure malnutrition, overweight, and obesity (11)(12)(13). Studies have shown that an increase in BMI increases the risk of cardiovascular disease (hypertension, myocardial infarction, lung disease, sleep apnea syndrome) (14).…”
Section: Introductionmentioning
confidence: 99%
“…Mediating variables included cognitive ability and Physical fitness, where the CEPS questionnaire was used to test students’ logical thinking and problem-solving ability to reflect their cognitive level. Physical fitness was primarily assessed using height and weight data to calculate BMI scores, and based on the BMI formula and BMI classification standard, participants within the normal BMI range were assigned a score of 1, and others were assigned a score of 0 ( Shen and Ma, 2022 ; Zhang et al, 2022 ). This was mainly because higher BMI scores are strongly associated with mortality ( Xiang et al, 2022 ), and BMI scores can be used to evaluate student Physical fitness status and serve as a convenient method for measuring student Physical fitness ( Han et al, 2022 ; Liu et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The theory of planned behavior holds that human behavior is the result of deliberate planning. Therefore, exercise intention can predict the generation of exercise behavior, and a large number of studies have confirmed that exercise intention is an effective predictor of exercise behavior Teixeira et al, 2022;Zhang et al, 2022). Hou et al (2022) confirmed in a study of 242 college students in China that exercise intention can effectively predict exercise behavior.…”
Section: Exercise Intention and Exercise Behaviormentioning
confidence: 98%